2018
DOI: 10.1111/1754-9485.12805
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of metabolic tumour volume and total lesion glycolysis measured by 18F‐fluorodeoxyglucose positron emission tomography/computed tomography in small cell lung cancer: A systematic review and meta‐analysis

Abstract: High MTV is associated with a significantly poorer prognosis OS and PFS, and high TLG is associated with a significantly poorer prognosis regarding OS for SCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Just like any other type of cancer, SCLC cells use aerobic glycolysis as the main source of adenosine triphosphate [ 70 ]. Notably, higher total lesion glycolysis (TLG) is correlated with poorer prognosis of SCLC [ 71 ]. A-disintegrin-and-metalloproteinase 12-s (Adam12S), a protein related to tissue growth and development, promoted SCLC cell proliferation, migration, and invasion by upregulating the rate-limiting enzyme hexokinase 1 in glycolysis [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Just like any other type of cancer, SCLC cells use aerobic glycolysis as the main source of adenosine triphosphate [ 70 ]. Notably, higher total lesion glycolysis (TLG) is correlated with poorer prognosis of SCLC [ 71 ]. A-disintegrin-and-metalloproteinase 12-s (Adam12S), a protein related to tissue growth and development, promoted SCLC cell proliferation, migration, and invasion by upregulating the rate-limiting enzyme hexokinase 1 in glycolysis [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, six meta-analyses containing information on the prognostic value of PET with different radiopharmaceuticals in patients with NETs and NECs were included (Table 2) [8,12,17,20,27,41]. These evidence-based manuscripts provided quantitative data about the prognostic value of 68 Ga-SSA PET or 18 F-FDG PET in patients with thoracic and/or gastroenteropancreatic NETs [8,17,20] or SCLC [12,27,41] in terms of disease control rate (DCR), event-free survival (EFS), progression-free survival (PFS) or overall survival (OS).…”
Section: Prognostic Value Of Pet With Different Radiopharmaceuticals In Neuroendocrine Neoplasmmentioning
confidence: 99%
“…Three different meta-analyses clearly demonstrated that 18 F-FDG PET has a significant prognostic value in patients with SCLC, in particular taking into account metabolic parameters at PET such as SUVmax of the primary lesion, metabolic tumor volume (MTV) or total lesion glycolysis (TLG) [12,27,41]. Higher values of these metabolic parameters were associated with a poorer prognosis regarding EFS, PFS and OS [12,27,41].…”
Section: Small Cell Lung Cancer (Sclc)mentioning
confidence: 99%
“… 2 In addition to the maximum SUV, state-of-the-art metrics for assessing tumor burden also include the metabolic tumor volume (MTV) and total lesion glycolysis (TLG). 3 Although this information is, in principle, available in routine examinations, the evaluation can imply the manual analysis of a large number of single lesions and thus proves to be problematic in everyday clinical practice and in the exploration of large cohorts. Computer-aided automatic detection and segmentation of tumor lesions is therefore of great importance in PET/CT imaging.…”
Section: Introductionmentioning
confidence: 99%